Removal of Methylene Blue Dye from Synthetic Wastewater using Kenaf Core and Activated Carbon - Ethaib, Saleem; K. Erabee, Iqbal; A. Abdulsahib, Ali (International Journal of Engineering and Technology, 2018)
The removal of textile-based cationic methylene blue (MB) dye from synthetic wastewater was investigated in batch model using low cost agro-based adsorbents named Kenaf core, and the activated carbon. A comparative analysis between these adsorbents was defined via pH, adsorbent dose and contact time on adsorption process, and morphological properties. In addition, isotherms adsorption studies were estimated for determination of the equilibrium adsorption capacity. The experimental observation showed that the optimum pH values for Kenaf core and the activated carbon were 6 and 4 respectively. Meanwhile the optimum adsorbent dosage values for Kenaf and the activated carbon were 1.5g for both. The results showed that a high adsorption efficiency for Kenaf core which was about 84% and 92 % for activated carbon. The correlation coefficients (ð‘…2) for kenaf core were equal to 0.8789 and 89 for Langmuir and Freundlich isotherm, respectively. Meanwhile, the correlation coefficients (ð‘…2) for activated carbon were equal were 0.8974 and 0.7643 for Langmuir and Freundlich isotherms, respectively. The results illustrated that the Kenaf core has a porous and an irregular surface area which make it a suitable adsorbent for dyes in the wastewater.Â